RAD51 and RAD51B Play Diverse Roles in the Repair of DNA Double Strand Breaks in Physcomitrium patens - Angelis, Karel J; Záveská Drábková, Lenka; Vágnerová, Radka; Holá, Marcela (Genes, 2023)
RAD51 is involved in finding and invading homologous DNA sequences for accurate homologous recombination (HR). Its paralogs have evolved to regulate and promote RAD51 functions. The efficient gene targeting and high HR rates are unique in plants only in the moss Physcomitrium patens (P. patens). In addition to two functionally equivalent RAD51 genes (RAD1-1 and RAD51-2), other RAD51 paralogues were also identified in P. patens. For elucidation of RAD51's involvement during DSB repair, two knockout lines were constructed, one mutated in both RAD51 genes (Pprad51-1-2) and the second with mutated RAD51B gene (Pprad51B). Both lines are equally hypersensitive to bleomycin, in contrast to their very different DSB repair efficiency. Whereas DSB repair in Pprad51-1-2 is even faster than in WT, in Pprad51B, it is slow, particularly during the second phase of repair kinetic. We interpret these results as PpRAD51-1 and -2 being true functional homologs of ancestral RAD51 involved in the homology search during HR. Absence of RAD51 redirects DSB repair to the fast NHEJ pathway and leads to a reduced 5S and 18S rDNA copy number. The exact role of the RAD51B paralog remains unclear, though it is important in damage recognition and orchestrating HR response.
Keywords: Rad51 Recombinase; homologní rekombinace; non-homologous end-joining (NHEJ); DNA, Ribosomal; DNA Breaks, Double-Stranded; dvouřetězcové zlomy DNA; genový targeting; rekombinasa Rad51; DNA double-strand break (DSB); bleomycin; repair kinetic; Homologous Recombination; Physcomitrella; rDNA; Gene Targeting; comet assay; ribozomální DNA; homologous recombination (HR); evolutionary divergence